Dose Dependence of the Separate and Combined Impact of Copper-Oxide and Selenium-Oxide Nanoparticles on Oxygen Consumption by Cells With or Without the Background Action of Some Modulators of the Mitochondrial Respiratory Function - Tatiana V. Bushueva; Vladimir G. Panov; Ilzira A. Minigalieva; Larisa I. Privalova; Maria S. Vedernikova; Vladimir B. Gurvich; Marina P. Sutunkova; Boris A. Katsnelson (SAGE Publishing, 2023)
We had previously demonstrated on various stable cell cultures exposed to chemically different nanoparticles when assessing their cytotoxicity by different outcomes, dose-response relationships may be either monotonic or non-monotonic falling within an extended understanding of the hormesis paradigm. Presently, on human fibroblasts exposed to the copper-oxide and/or selenium-oxide nanoparticles, we assessed their cytotoxic effect by the inhibition of oxygen uptake against modulating the respiratory function of mitochondria (oligomycin, followed by carbonyl cyanide-4-(trifluoromethoxy) phenylhydrazone, and, finally, rotenone with antimycin A). It is hypothesized that a given type of this relationship is closely associated with the mitochondrial respiratory function. However, in only one case, this hypothesis was confirmed by finding that the monotonic dose-response relationship transformed into a non-monotonic one of the hormesis type under exposure to SeO-NP with the mitochondrial respiratory function fully inhibited by the effect of rotenone + antimycin А. In all other variants of the experiment, the shape of this relationship did not depend on the addition of the above agents to the cell culture. Neither did the effect of these modulators change the pattern of combined action of CuO-NP and SeO-NP, which was additive in all cases.